THE SEMANTIC FIELD OF “LOVE” IN JAVANESE LANGUAGE - Hendryanto, Larasati Mauli Amane; Widhyasmaramurti, Widhyasmaramurti (UI Scholars Hub, 2024)
This research delves into the extensive lexicon of the Javanese language, specifically focusing on expressions related to feelings of love. The presence of multiple Javanese lexicons denoting love poses a significant challenge, prompting the central question: What are the semantic nuances that distinguish each lexicon, given the absence of absolute synonyms? The research aims to elucidate the semantic fields that differentiate each love-related lexicon in Javanese. Data for this research is drawn from four distinct Javanese dictionaries, spanning various publication periods. Additionally, the study incorporates diverse data sources, including a book titled